Rapid transient and longer-lasting innate cytokine changes associated with adaptive immunity after repeated SARS-CoV-2 BNT162b2 mRNA vaccinations - Rosati, Margherita; Terpos, Evangelos; Homan, Philip; Bergamaschi, Cristina; Karaliota, Sevasti; Ntanasis-Stathopoulos, Ioannis; Devasundaram, Santhi; Bear, Jenifer; Burns, Robert; Bagratuni, Tina; Trougakos, Ioannis P.; Dimopoulos, Meletios A.; et al. (Frontiers in Immunology, 2023)
Introduction: Cytokines and chemokines play an important role in shaping innate and adaptive immunity in response to infection and vaccination. Systems serology identified immunological parameters predictive of beneficial response to the BNT162b2 mRNA vaccine in COVID-19 infection-naïve volunteers, COVID-19 convalescent patients and transplant patients with hematological malignancies. Here, we examined the dynamics of the serum cytokine/chemokine responses after the 3rd BNT162b2 mRNA vaccination in a cohort of COVID-19 infection-naïve volunteers. Methods: We measured serum cytokine and chemokine responses after the 3rd dose of the BNT162b2 mRNA (Pfizer/BioNtech) vaccine in COVID-19 infection-naïve individuals by a chemiluminescent assay and ELISA. Anti-Spike binding antibodies were measured by ELISA. Anti-Spike neutralizing antibodies were measured by a pseudotype assay. Results: Comparison to responses found after the 1st and 2nd vaccinations showed persistence of the coordinated responses of several cytokine/chemokines including the previously identified rapid and transient IL-15, IFN-γ, CXCL10/IP-10, TNF-, IL-6 signature. In contrast to the transient (24hrs) effect of the IL-15 signature, an inflammatory/anti-inflammatory cytokine signature (CCL2/MCP-1, CCL3/MIP-1, CCL4/MIP-1, CXCL8/IL-8, IL-1Ra) remained at higher levels up to one month after the 2nd and 3rd booster vaccinations, indicative of a state of longer-lasting innate immune change. We also identified a systemic transient increase of CXCL13 only after the 3rd vaccination, supporting stronger germinal center activity and the higher anti-Spike antibody responses. Changes of the IL-15 signature, and the inflammatory/anti-inflammatory cytokine profile correlated with neutralizing antibody levels also after the 3rd vaccination supporting their role as immune biomarkers for effective development of vaccine-induced humoral responses. Conclusion: These data revealed that repeated SARS-Cov-2 BNT162b2 mRNA vaccination induces both rapid transient as well as longer-lasting systemic serum cytokine changes associated with innate and adaptive immune responses. Clinical trial registration: Clinicaltrials.gov, identifier NCT04743388.